Qidfa' 1 : excavation of a late prehistoric tomb, Fujairah Emirate, United Arab Emirates - Al Tikriti, Walid Yasin, (Archaeopress Archaeology, 2022)
This volume presents results from the rescue excavations of the Qidfa' 1 site, a multi-period tomb (Wadi Suq-Late Bronze/Early Iron Age). The richness of the discoveries demonstrates the wealth and significance of the culture of the 2nd millennium BC in southeast Arabia.